Sportsmanship and basic psychological needs in sports students - Germina-Alina Cosma; Alina Chiracu; Amalia-Raluca Stepan; Roxana Gatzel; Augustin Iancu; Alexandru Cosma (Baltic Journal of Health and Physical Activity, 2021)
The aim of this study was to examine the relationships among satisfaction of basic psychological needs, goal orientations and sportsmanship. The mediating role of goal orientation in this relationship was tested. The participants were 168 students enrolled at the Faculty of Physical Education and Sports in Craiova, aged between 18 and 30 years old, M = 21.52, SD = 2.20, and the data were collected between March and May 2020. The instruments applied were Basic Psychological Needs Satisfaction Scale to measure satisfaction of basic psychological needs, Multidimensional Sportspersonship Orientation Scale to measure sportsmanship, and Ego and Task Orientation Questionnaire to measure goal orientation. The obtained results showed that the satisfaction of basic psychological needs is associated with sportsmanship. Mediation analyses have shown that task orientation mediates the relationship between the need for autonomy and the need for competence satisfaction and four of the dimensions of sportsmanship and the relationship between the need for relatedness satisfaction and three of sportsmanship dimensions: respect for social conventions, respect for rules and officials, and respect for full commitment.